(2x+y)-(x-4y)=

Simple and best practice solution for (2x+y)-(x-4y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+y)-(x-4y)= equation:


Simplifying
(2x + y) + -1(x + -4y) = 0

Remove parenthesis around (2x + y)
2x + y + -1(x + -4y) = 0
2x + y + (x * -1 + -4y * -1) = 0
2x + y + (-1x + 4y) = 0

Reorder the terms:
2x + -1x + y + 4y = 0

Combine like terms: 2x + -1x = 1x
1x + y + 4y = 0

Combine like terms: y + 4y = 5y
1x + 5y = 0

Solving
1x + 5y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5y' to each side of the equation.
1x + 5y + -5y = 0 + -5y

Combine like terms: 5y + -5y = 0
1x + 0 = 0 + -5y
1x = 0 + -5y
Remove the zero:
1x = -5y

Divide each side by '1'.
x = -5y

Simplifying
x = -5y

See similar equations:

| x+2=7 | | (9z^3+6z)-(-2z^3-4z+8)= | | x^5+3x^4+2x^3+2x^2+6x+4=0 | | 6(2a^2+3a)=6(3-2a) | | x^5+3x^4c+2x^3+2x^2+6x+4=0 | | -17=3-4n | | 2(-5-3a)=7a+3 | | x^3+8x^2-8x-64= | | ln(x+3)-ln(x-4)=ln(x) | | -32x^2-80x-32=0 | | 3(r+4)+2(r+5)=32 | | 3x-5y=22 | | 15n^2+16n-7=0 | | (9x-2)(9x+2)= | | 27x^3+1000=0 | | -9=2-(5-z) | | 7x^2+-14x-7=0 | | 4+30(12+36+60)=x | | -4(6-w)=-2w-12+4w | | 0.8b=10.4 | | 1+3(16-2x)=0 | | 1+3(16-2x)= | | x+15=-5 | | x^2-24x+108=0 | | 9=-5(4x+2)+21x | | 4x=5y-17 | | .75w+8=.3w-7 | | -2(2+5n)+16(5-9n)= | | -30=j | | 6a^2+6a=6+6a | | 14=j-44 | | x=3.14(36)8-3.14(16)8 |

Equations solver categories